A Feasibility Analysis of Tilapia (Oreochromis Niloticus) Grow-Out Cultivation at Pokdakan Minasari, Purwosari Village, Baturaden Sub-District, Banyumas Regency - Rahul Toni Ibrahim; Watemin watemin; Dumasari Lumongga; Pujiati Utami (UNIVED Press, Dehasen University Bengkulu, 2025)
Purpose: This study aims to determine the costs, revenues, income, and feasibility of tilapia fish farming in POKDAKAN Minasari, Purwosari Village, Baturaden District, Banyumas Regency. Methodology: This study uses a case study method. Informants in this study are members of POKDAKAN Minasari, Purwosari Village, Baturaden District, Banyumas Regency. This study uses a census method in sampling techniques. Data collection methods used include observation, interviews, and documentation to obtain eight respondents based on selection criteria. Results: This study shows that tilapia fish farming in POKDAKAN Minasari is in accordance with the procedure. The average total cost of tilapia fish farming reaches Rp 12,258,710, while the average business income is Rp 18,281,250. Findings: Water quality in the cultivation pond greatly affects the cultivation results, the better the water quality is maintained, the better the cultivation results will be because water quality affects the health of the fish. Conclusion: From this difference, the average income obtained is Rp 6,022,540. The tilapia cultivation business run by the Minasari Fish Farmers Group (POKDAKAN) in Purwosari Village, Baturaden District, Banyumas Regency, is considered feasible, with a R/C ratio of 1.49. The production break-even point (BEP) was recorded at 56 fish, while the BEP price was at Rp 16,770. Article Type: Research Article.